The LIGHT TRAFFIC MODELING AT UNSIGNALED INTERVIEWS USING THE PTV.VISSIM AND PKJI 2023 APPLICATION (Simpang 3 Jl. Sungai Rupat, Bengkulu City): PEMODELAN TRAFFIC LIGHT PADA SIMPANG TAK BERSINYAL MENGGUNAKAN APLIKASI PTV.VISSIM DAN PKJI 2023 (Simpang 3 Jl. Sungai Rupat Kota Bengkulu ) - pramudiya, chendi; Elly Pujiastutie; Edito Dwiantoro (Universitas Negeri Surabaya, 2025)
The unsignalized intersection on Jl. Sungai Rupat is type 322 intersection that has 3 intersection arms, 2 lanes on minor roads and 2 lanes on roads. At this 3-way intersection, it is an inner-city road that connects roads to the city center, hospitals, offices, school, and worship so has a fairly high density and ultimately the density of traffic volume becomes high. When the morning peak hour occurs, it will cause congestion so that the police are often involved to regulate traffic. This study aims to create a traffic light modeling using PTV Vissim and also the PKJI 2023 method. Data collection for 7 days during peak hours to find the highest traffic volume so that the data can be analyzed using the PKJI 2024 method and simulated using PTV Vissim. The highest traffic volume, namely Tuesday at peak hours in the morning at 7:30 - 9:00 with a traffic volume (Q) of 3450 sec/hour capacity (C) 2844 sec/hour, queue opportunity of 60.08%-122.39% and a delay of 43.65 sec/sec with intersection service level (LOS) E. And the modeling results obtained Delay results at 15.43 sec/sec with a queue length of 11.50-44.79 m with an intersection service level index (LOS) B.